Echeverría y Unamuno, barroco y agonismo. Una articulación del ethos barroco y el ethos trágico - Beraldi, Gastón (2023)
This paper seeks to sketch a possible articulation of the tragic ethos and the baroque ethos. The starting point is Echeverría’s hypothesis concerning the baroque character of Unamuno’s Quijote. I argue that such a baroque ethos an attitude, a behaviour, and a vital strategy as defined by the Ecuadorian philosopher, goes beyond Unamuno’s Quijote, and is linked to the tragic ethos of Unamuno’s agonism. I follow Saéz Rueda’s hypothesis that, on the one side, Unamuno’s agonism is closely related to the baroque attitude and, on the other side, that there are at least two unifying bonds between the Baroque and the tragic. I propose that it is possible to add two more bonds. The first one has to do with the understanding of action shared by Echevarría and Unamuno, the choice of a third that cannot be. The second bond considers that such a community of attitude, of ethos, between the tragic and the Baroque can be established from the moral pedagogic function of the tragic and baroque works